2006
DOI: 10.1590/s0101-81752006000300014
|View full text |Cite
|
Sign up to set email alerts
|

Scorpions from Mata do Buraquinho, João Pessoa, Paraíba, Brazil, with ecological notes on a population of Ananteris mauryi Lourenço (Scorpiones, Buthidae)

Abstract: ABSTRACT. Four species of scorpions (Ananteris mauryi Lourenço, 1982, Tityus neglectus Mello-Leitão, 1932, T. pusillus Pocock, 1893 and T. stigmurus (Thorell, 1876) were collected in the "Mata do Buraquinho", João Pessoa, state of Paraíba, Brazil. Aspects of biology for A. mauryi and new records on the geographic distribution of other species were annotated. Notes on the abundance and sex ratio on A. mauryi, the most abundant species in the area, are presented and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 9 publications
1
9
2
2
Order By: Relevance
“…Soil type, topography, hydrology, soil humidity, food resources, and especially temperature and precipitation (Polis ; Dias et al. ; Yamaguti & Pinto‐da‐Rocha ) have been shown to affect scorpion activity in arid region ecosystems. Temperature profoundly affects many processes, including growth (Angilletta et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Soil type, topography, hydrology, soil humidity, food resources, and especially temperature and precipitation (Polis ; Dias et al. ; Yamaguti & Pinto‐da‐Rocha ) have been shown to affect scorpion activity in arid region ecosystems. Temperature profoundly affects many processes, including growth (Angilletta et al.…”
mentioning
confidence: 99%
“…Daily and seasonal patterns of scorpion activity are affected by both biological factors (e.g., the presence of predators, prey, or potential mates) and environmental factors (Polis 1990;Hoshino et al 2006). Soil type, topography, hydrology, soil humidity, food resources, and especially temperature and precipitation (Polis 1990;Dias et al 2006;Yamaguti & Pinto-da-Rocha 2006) have been shown to affect scorpion activity in arid region ecosystems. Temperature profoundly affects many processes, including growth (Angilletta et al 2004), locomotor performance (Forsman 1999), and surface activity (Bradley 1988).…”
mentioning
confidence: 99%
“…For example, in a 24 month study performed in a caatinga fragment, Araújo et al (2010) recorded only 104 individuals of four species, all of which are reported here. Also, Dias et al (2006) reported only 72 specimens belonging to four species in an urban rainforest fragment in Northeastern Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…We installed the drift fences close to the ground to drive the local fauna towards the traps and increase the capture sampling (Ellis & Bedward, ). Pitfalls are widely used for sampling scorpions and harvestmen in taxonomic and ecological studies, including as the only sampling method (Dias et al., ; Freire & Motta, ). These traps have made it possible to test relevant ecological hypotheses in tropical forest environments (Lo‐Man‐Hung, Gardner, Ribeiro, Barlow, & Bonaldo, ; Uehara‐Prado et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…We chose harvestmen (Arachnida: Opiliones) and scorpions (Arachnida: Scorpiones) to evaluate the three methods for the following reasons: (1) detailed ecophysiological or behavioural data about the species are rare, and if any of these investigated models based on distribution information is adequate, these arachnids have its potential for use in ecological studies improved (2) species have different range sizes, occurrence patterns in biomes and specialization in habitat use on a local scale (Bragagnolo, Nogueira, Pinto‐da‐Rocha, & Pardini, ; Dias, Candido, & Brescovit, ; Kury, ; Lira & DeSouza, ; Uehara‐Prado et al., ), which allows for important variation in the investigated variables; and (3) their taxonomy is well known (Lourenço, ; Pinto‐da‐Rocha, Machado, & Giribet, ; Porto, Brazil, & Souza, ), which allows for specific determinations to be consistent with the species names used in the literature.…”
Section: Introductionmentioning
confidence: 99%